Discovery of 4, 6-disubstituted pyrimidines as potent inhibitors of the heat shock factor 1 (HSF1) stress pathway and CDK912. Issue 8 (20th June 2016) - Rye, Carl S.; Chessum, Nicola E. A.; Lamont, Scott; Pike, Kurt G.; Faulder, Paul; Demeritt, Julie; Kemmitt, Paul; Tucker, Julie; Zani, Lorenzo; Cheeseman, Matthew D.; Isaac, Rosie; Goodwin, Louise; et al.
Abstract : A series of 4, 6-disubstituted pyrimidines from a phenotypic screen targeting the HSF1 pathway are also potent inhibitors of CDK9. Abstract : Heat shock factor 1 (HSF1) is a transcription factor that plays key roles in cancer, including providing a mechanism for cell survival under proteotoxic stress. Therefore, inhibition of the HSF1-stress pathway represents an exciting new opportunity in cancer treatment. We employed an unbiased phenotypic screen to discover inhibitors of the HSF1-stress pathway. Using this approach we identified an initial hit (1 ) based on a 4, 6-pyrimidine scaffold (2.00 μM). Optimisation of cellular SAR led to an inhibitor with improved potency (25, 15 nM) in the HSF1 phenotypic assay. The 4, 6-pyrimidine25 was also shown to have high potency against the CDK9 enzyme (3 nM).